(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2023)
The discoursal web is enabled by the very nature of the PU: cohesion of its base form. Signals of phraseological presence work like a cohesive framework. Instantial use may provide cohesion across not only sentences and paragraphs, but also larger stretches of text. The PU, some part or separate constituents of it, cannot be interpreted without the complete extent of instantial use. The structure of discourse depends on a balance between all base and instantial elements interlinked by phraseological ties. Any change in the PU, for instance, replacement of one instantial pattern by another, let alone replacement of instantial use by core use, would change the entire network of relationships and hence meaning. Phraseological cohesion is central to interpretation of a stretch of discourse